Learning Culture and Computational Thinking in a Spanish Course: A Development Model. (September 2021) - Zha, Shenghua; Morrow, Debra A. L.; Curtis, Jennifer; Mitchell, Shane
Computer science and computational thinking (CT) education in K-12 schools have been escalating in recent years. A couple of CT instructional models have been proposed to depict the roles of CT in K-16 education. Yet, neither of them discussed CT infusion into a subject course. In this article, we proposed a CT-integration model called TPC 2 T. In this model, we suggested considering CT as a second subject and using an appropriate technological pedagogical approach to make students' learning of two subjects meaningful and engaging. We implemented this model in a CT-integrated lesson in two sections of a high-school Spanish course. Students worked in small groups and coded three small and one comprehensive digital Spanish-culture stories in Scratch. Results showed that students taking the CT-integrated lesson had the same degree of improvement in their Spanish culture knowledge as their peers who did not take the CT-integrated lesson. Besides, students taking the CT-integrated lesson had a significant improvement in their CT knowledge. At the same time, their CT self-efficacy outperformed those who did not take the CT-integrated lesson. We discussed the results and offered suggestions for researchers and educators at the end of the article.